2022
DOI: 10.21037/atm-22-2847
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety of caplacizumab versus placebo in thrombotic thrombocytopenic purpura: a meta-analysis and systematic review based on randomized controlled trials

Abstract: Background: We conducted this meta-analysis to investigate the efficacy and safety of caplacizumab in patients with thrombotic thrombocytopenic purpura (TTP). TTP is a potentially fatal disorder characterized by systemic microvascular thrombosis.Methods: Randomized controlled trials (RCTs) were conducted from PubMed, Embase, Cochrane Library and Web of Science, China National Knowledge Infrastructure (CNKI), VIP and Wanfang databases. RCTs of caplacizumab treatment for TPP were mainly included. Data from eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…None of the studies showed a difference in death rates between the group caplacizumab and group placebo. In the same way, Djulbegovic et al and Chen et al found a similar conclusion that caplacizumab's reduction in death estimates was not significant [20,21].…”
Section: Discussionmentioning
confidence: 62%
“…None of the studies showed a difference in death rates between the group caplacizumab and group placebo. In the same way, Djulbegovic et al and Chen et al found a similar conclusion that caplacizumab's reduction in death estimates was not significant [20,21].…”
Section: Discussionmentioning
confidence: 62%
“…Acquired thrombotic thrombocytopenic purpura (aTTP) is a thrombotic microangiopathy caused by severely reduced ADAMTS13 activity. 1,2 Usually, this is mediated by autoantibodies that target ADAMTS13, a protease responsible for cleaving von Willebrand factors (vWF). The absence of ADAMTS13 results in the circulation of ultralarge vWF multimers, which leads to thrombotic emergencies and a mortality rate up to 15% to 20%.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of ADAMTS13 results in the circulation of ultralarge vWF multimers, which leads to thrombotic emergencies and a mortality rate up to 15% to 20%. 2,3 Caplacizumab is an anti-vWF monoclonal antibody approved in 2019 by the US Food and Drug Administration and European Medicines Agency for the treatment of aTTP in adults. It has demonstrated faster platelet normalization, clinical improvement, and reduced risk of recurrent or refractory disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations